Evoking emotional states in personality disordered offenders: An experimental pilot study of experiential drama therapy techniques. (April 2017) - Keulen-de Vos, Marije; van den Broek, Elsa P.A.; Bernstein, David P.; Vallentin, Roos; Arntz, Arnoud
Highlights: A pilot study on eliciting emotions through drama therapy techniques is presented. Participants showed significantly more vulnerable emotions after the intervention. Emotions can be evoked and treated in forensic clients, including psychopaths Abstract: Offenders with personality disorders (PDs) and the crimes that they have committed are regularly associated with emotional deficits. A renewed focus in forensic treatment is the use of experiential techniques: techniques that have a strong focus on eliciting emotions. However, there is little empirical evidence on the effectiveness of experiential techniques in forensic clients with PDs. In our pilot study, we examined whether three experiential drama therapy interventions are effective in evoking emotional vulnerability and anger in nine offenders with cluster B PDs, that is, clients with DSM-IV Antisocial, Borderline, or Narcissistic PDs. We used a 5 session drama therapy protocol that consisted of an introduction session, a general experiential session, a session to evoke emotional vulnerability, a session to evoke anger, and a wrap-up session. Emotions were assessed using the Mode Observation Scale. Participants showed significantly more emotional vulnerability within all three experiential invention sessions, comparing peak mood after the experiential intervention was initiated to baseline mood. In contrast, clients did not show more anger after the session to evoke anger, or in the other two experiential sessions. Our findings, though preliminary, suggest that experiential drama therapy methods may be effective in evoking vulnerable emotional states in forensic clients with cluster B personality disorders. We discuss the clinical implications of these findings.